Immunogenicity and antitumor efficacy of a novel human PD-1 B-cell vaccine (PD1-Vaxx) and combination immunotherapy with dual trastuzumab/pertuzumab-like HER-2 B-cell epitope vaccines (B-Vaxx) in a syngeneic mouse model. (1st January 2020) - Kaumaya, Pravin T. P.; Guo, Linlin; Overholser, Jay; Penichet, Manuel L.; Bekaii-Saab, Tanios
ABSTRACT: Therapeutic blockade of PD-1/PD-L1 signaling with monoclonal antibodies (mAbs) has shown clinical success and activity across a broad set of cancer subtypes. However, monotherapy with PD-1/PD-L1 inhibitors are only effective in a subset of patients and ongoing studies show efficacy of treatment depends on a combinatorial approach. Contrary to mAbs chimeric B-cell cancer vaccines incorporating a "promiscuous" T-cell epitope have the advantage of producing a polyclonal B-cell antibody that can potentially induce memory B- and T-cell responses, while reducing immune evasion and suppression. Here, we describe a novel PD-1 B-cell peptide epitope vaccine (amino acid 92–110; PD1-Vaxx) linked to a measles virus fusion peptide (MVF) amino acid 288–302 via a four amino acid residue (GPSL) emulsified in Montanide ISA 720VG that aims to induce the production of polyclonal antibodies that block PD-1 signaling and thus trigger anticancer effects similar to nivolumab. In preclinical studies, the PD1-Vaxx outperformed the standard anti-mouse PD-1 antibody (mAb 29F.1A12) in a mouse model of human HER-2 expressing colon carcinoma. Furthermore, the combination of PD1-Vaxx with combo HER-2 peptide vaccine (B-Vaxx) showed enhanced inhibition of tumor growth in colon carcinoma BALB/c model challenged with CT26/HER-2 cells. The PD-1 or combined vaccines were safe with no evidence of toxicity or autoimmunity.